2002
DOI: 10.1073/pnas.182203999
|View full text |Cite
|
Sign up to set email alerts
|

ENSO and cholera: A nonstationary link related to climate change?

Abstract: We present here quantitative evidence for an increased role of interannual climate variability on the temporal dynamics of an infectious disease. The evidence is based on time-series analyses of the relationship between El Niñ o͞Southern Oscillation (ENSO) and cholera prevalence in Bangladesh (formerly Bengal) during two different time periods. A strong and consistent signature of ENSO is apparent in the last two decades (1980 -2001), while it is weaker and eventually uncorrelated during the first parts of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
228
1
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 256 publications
(243 citation statements)
references
References 33 publications
12
228
1
2
Order By: Relevance
“…25,26 In recent years, numerous studies have demonstrated the association between the re-emergence and dynamics of infectious diseases and environmental factors. 7,27 We identified such an association between temperature and rainfall and the increase in the number of cholera cases in three outbreaks occurring in Lusaka (2003Lusaka ( -2006, which is in concordance with suggested environmental theories for re-emergence of infectious diseases. It is worth noting that most studies relating climate to cholera describe coastal regions.…”
Section: Discussionsupporting
confidence: 82%
“…25,26 In recent years, numerous studies have demonstrated the association between the re-emergence and dynamics of infectious diseases and environmental factors. 7,27 We identified such an association between temperature and rainfall and the increase in the number of cholera cases in three outbreaks occurring in Lusaka (2003Lusaka ( -2006, which is in concordance with suggested environmental theories for re-emergence of infectious diseases. It is worth noting that most studies relating climate to cholera describe coastal regions.…”
Section: Discussionsupporting
confidence: 82%
“…Laboratory experiments showed a positive correlation between temperature and the metabolic activity of V. cholerae O1 in defined sea salt solution in a temperature range from 10 to 25 u C (Singleton et al, 1982a). Furthermore, a more frequent detection of V. cholerae O1 in estuary waters and a higher morbidity rate among people in Bangladesh was shown to be associated with increasing temperatures (Louis et al, 2003;Rodo et al, 2002).…”
Section: Introductionmentioning
confidence: 98%
“…S cientists have described a wide range of potential negative impacts of climate change 1 on many vulnerable aspects of natural systems and human populations 2,3 , and particularly the sensitivity of our society to atmospheric temperatures 4,5 . In particular, increasing attention has been paid to warm extremes [6][7][8][9][10] , which are expected to become more frequent, longer and more severe 11 .…”
mentioning
confidence: 99%